(3JaSjQ GdLRA GdCNjQ ef GdbQBfs - (3jMji Hf GdaQGA, CHh RcQjGs
(3ChdgG (B:s
(3GdMeO ddg JYGdi hMOg hef ShQI YHS (B" (3HSe Gddg GdQMef GdQMje YHS hJhdi s
(3BNQgG (B:s
(3bHSeG QLGd ef GdLf hGdGfS hGddg GYde JeJ gPg GdfSNI GdeHGQcI HMeO Gddg hcGf GdaQGZ s
(3HgG KdGK hbaGJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JaSjQ (B11) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs